PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN PEMASOK NATA DE COCO DI PT. XZY - Dian Eko Hari Purnomo (Universitas Sarjanawiyata Tamansiswa, 2016)
PT. XYZ is a manufacturing company that produces nata de coco pieces. Consumers of the product nata de coco pieces of food businesses such as food PT.Garuda Sidoarjo, PT. Holy Sinar Mas, PT. Borobudur Semarang and others. PT. XYZ has two types of contract supplier and the supplier is not a contract. Currently, the company in the selection of suppliers do not contract into supplier contracts sometimes have trouble. Terebut difficulties occurred because of the detailed criteria that can be used for the selection of suppliers. So in this study will berusahaan find criteria that influence supplier selection. The data in this study using the method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). In addition, models that have been made will be implemented into a Decision Support System (DSS). The criteria that can mempengeruhi supplier selection is the sum total, the number of total quality one, a total of two quality, the total number of nata broken, the number of deliveries the maximum, the maximum number of quality one, the maximum number of two qualities, the maximum amount is broken, the number of deliveries at a minimum, the number of minimum quality one, the minimum number two quality, the minimum amount is broken, regularity, quality price and the price of the quality of the two. In addition, based on test results Decision Support System (DSS), which has made the conclusion that the system that has been created can be used later by PT. XYZ.